TRIP’S Agreement in Legal Protection of Intellectual Property Rights in Indonesia - Bayu Abdillah (Rechtenstudent, 2024)
Before Indonesia ratified the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement), the national legal system had recognized regulations regarding Intellectual Property Rights (IPR) inherited from the Dutch East Indies colonial era. During that period, the applicable regulations still referred to the Dutch legal system enforced in the colonial territories, including Indonesia. The scope of IPR protection at that time was limited to three main aspects, namely copyright, trademarks and industry, and patents. However, the ratification of the TRIPS Agreement by Indonesia was an important milestone in the transformation of national IPR law. Since then, there has been a significant expansion in the scope, definition, and protection system for various forms of intellectual property. This regulatory update reflects Indonesia's commitment to aligning its legal system with international standards, while strengthening its position in the global trade order. This study aims to analyze the influence of the TRIPS Agreement on the development of IPR legislation in Indonesia, and to assess the extent to which its implementation provides certainty and legal protection for rights owners. Through a normative approach with historical analysis and comparative law, this study emphasizes the importance of harmonizing national law with international instruments in order to support a fair and sustainable investment and trade climate.